Interaction of Electron with its Own Electric Field - Rahemi, H. (Asian Journal of Chemistry, 2010)
Interaction of electron with its own electric field is included in the Hartree-Fock-Roothaan theory. Coulomb integrals were calculated by interacting the charge density probabilities of all electrons in two volume elements of space and then it is extented over all space. Helium electronic ground state is studied by the use of the double zeta and panta zeta Slater-type orbitals as a basis set of functions. Imperical internal electronic coupling constant ξ, is introduced and its negative value indicate that interaction with self electric field is a kind of attractive (cohesion) force.